2019
DOI: 10.1039/c9dt02353d
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(ii) and palladium(ii) homo- and heterobimetallic complexes: synthesis, crystal structures, theoretical calculations and biological studies

Abstract: Four Ru–Pd heterobimetallic complexes, each one in two different coordination modes (NNSS and NS) were prepared of dialkyldithiooxamidate ligands. All stable NS complexes showed anti-proliferative activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…We chose this new ligand to explore whether steric effects of the methyl group in proximity to the bridge would reduce the number of isomers synthesized, or whether the mixture of isomers produced could be successfully separated into isolated isomers. While diiridium complexes with μ 2 ‐dithioxamidato ligand [ anti S 2 C−CN 2 ] or [ syn S 2 C−CN 2 ] as the bridge have not been reported, the structures of diruthenium and dipalladium complexes with a substituted μ 2 ‐dithioxamidato [ anti SNC−CNS] bridge have been determined elsewhere [32,33] . Although the isomers formed could not be isolated pure, we show the remarkable structural diversity of the syn and anti isomers from X‐ray crystallography on crystals grown from isomeric mixtures containing complexes 3 a – d , 4 and 5 .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…We chose this new ligand to explore whether steric effects of the methyl group in proximity to the bridge would reduce the number of isomers synthesized, or whether the mixture of isomers produced could be successfully separated into isolated isomers. While diiridium complexes with μ 2 ‐dithioxamidato ligand [ anti S 2 C−CN 2 ] or [ syn S 2 C−CN 2 ] as the bridge have not been reported, the structures of diruthenium and dipalladium complexes with a substituted μ 2 ‐dithioxamidato [ anti SNC−CNS] bridge have been determined elsewhere [32,33] . Although the isomers formed could not be isolated pure, we show the remarkable structural diversity of the syn and anti isomers from X‐ray crystallography on crystals grown from isomeric mixtures containing complexes 3 a – d , 4 and 5 .…”
Section: Introductionmentioning
confidence: 77%
“…While diiridium complexes with μ 2 -dithioxamidato ligand [anti S 2 CÀ CN 2 ] or [syn S 2 CÀ CN 2 ] as the bridge have not been reported, the structures of diruthenium and dipalladium complexes with a substituted μ 2 -dithioxamidato [anti SNCÀ CNS] bridge have been determined elsewhere. [32,33] Although the isomers formed could not be isolated pure, we show the remarkable structural diversity of the syn and anti isomers from X-ray crystallography on crystals grown from isomeric mixtures containing complexes 3 a-d, 4 and 5. The syn isomers of μ 2oxamidato-bridged diiridium systems are reported here for the first time.…”
Section: Introductionmentioning
confidence: 79%
“…On the basis of our ongoing research work dealing with Ru-based complexes, , we determined to evaluate this newly synthesized panel of compounds as anticancer agents. Specifically, we employed two leukemic cell lines well established in our previous works, namely CCRF-CEM (drug-sensitive) and CEM/ADR5000 (CCRF-CEM multidrug-resistant subcell line).…”
Section: Resultsmentioning
confidence: 99%
“…Two auxiliary salicylaldehyde ligands with different pattern of substitution and the starting Ru­(phen) 2 Cl 2 complex were selected as controls. We did not use the standard Ru-based complex NAMI-A as a positive control as our previous studies demonstrated that this compound exerts negligible cytotoxic effects against the two selected leukemic cell lines Figure shows the screening results sorted by decreasing cell viability (waterfall plot).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these arguments, we have further explored whether a selected group of metal compounds might contrast the growth of leukemia cells in vitro as well as inhibit potently and selectively the main protease activities of the proteasome. Previous results showed that, in general, metal-based compounds endowed with anticancer activity may behave as strong proteasome inhibitors [ 14 , 15 , 16 ]. In particular, pertaining to anticancer gold derivatives, we reported that a group of gold(III) complexes and a gold(I) phosphine complex caused profound and differential inhibition of this target, at variance with the reference compound AF, which turned out to be nearly ineffective [ 17 ].…”
Section: Introductionmentioning
confidence: 99%